2016
DOI: 10.1038/srep39232
|View full text |Cite
|
Sign up to set email alerts
|

An adenylyl cyclase with a phosphodiesterase domain in basal plants with a motile sperm system

Abstract: Adenylyl cyclase (AC), which produces the signalling molecule cAMP, has numerous important cellular functions in diverse organisms from prokaryotes to eukaryotes. Here we report the identification and characterization of an AC gene from the liverwort Marchantia polymorpha. The encoded protein has both a C-terminal AC catalytic domain similar to those of class III ACs and an N-terminal cyclic nucleotide phosphodiesterase (PDE) domain that degrades cyclic nucleotides, thus we designated the gene MpCAPE (COMBINED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…Again, much like in the case of the cyclases, a BLAST search with an annotated C. reinhardtii PDE (A8HNW2_CHLRE) does not return any plausible candidate with reasonable similarity. However, recently a liverwort ( Marchantia polymorpha ) protein has been reported that has both AC and PDE domain and both activities ( Kasahara et al, 2016 ). Incidentally, the molecule does contain an AC catalytic center motif ([RKS]X[CTGH]X{8,12}[KR]X{1,3}[DE]) but has no ortholog in Arabidopsis or other higher plants for that matter.…”
Section: Out-lookmentioning
confidence: 99%
“…Again, much like in the case of the cyclases, a BLAST search with an annotated C. reinhardtii PDE (A8HNW2_CHLRE) does not return any plausible candidate with reasonable similarity. However, recently a liverwort ( Marchantia polymorpha ) protein has been reported that has both AC and PDE domain and both activities ( Kasahara et al, 2016 ). Incidentally, the molecule does contain an AC catalytic center motif ([RKS]X[CTGH]X{8,12}[KR]X{1,3}[DE]) but has no ortholog in Arabidopsis or other higher plants for that matter.…”
Section: Out-lookmentioning
confidence: 99%
“…Additionally, components of cAMP signaling pathways, as well as cAMP interacting proteins (i.e., ACs, phosphodiesterases (PDEs) and protein kinase A (PKA)) have been reported ( Assmann, 1995 ; Gehring, 2010 ; Donaldson et al, 2016 ). To date, however, no gene encoding a PDE has been identified in higher angiosperms, although a recent study has identified a class III AC in the liverwort Marchantia polymorpha which also harbors a functional N-terminal PDE domain ( Kasahara et al, 2016 ). This protein has orthologs only in basal land plants and charophytes, thus a bona fide PDE-AC in higher plants remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…This GC-derived AC motif has further identified a functional AC center in a pentatricopeptide repeat-containing protein (AtPPR) [ 92 ] and predicted several candidate ACs in Arabidopsis thaliana [ 15 , 17 ] some of which are currently under experimental evaluation. Recently, a functional AC domain that contains the AC catalytic center motif has been reported in liverwort Marchantia polymorpha and interestingly, this protein also harbors a phosphodiesterase (PDE) domain that is capable of degrading cyclic nucleotide monophosphates [ 93 ] thus representing an example of a complex multi-domain plant protein capable of regulating cellular cyclic nucleotide monophosphates levels. However, this protein has orthologues only in basal land plants and charophytes that use motile sperms as the male gamete [ 93 ] and thus a bona fide PDE-AC in higher plants remains elusive.…”
Section: Nucleotide Cyclase Functional Centers In Plantsmentioning
confidence: 99%